2016
DOI: 10.1002/cpmb.25
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Primary Fibroblast Culture from Wildlife: the Panthera onca Case to Preserve a South American Endangered Species

Abstract: Cell line establishment of somatic cells is a valuable resource to preserve genetic material of rare, difficult-to-find, endangered and giant species like Jaguar (Panthera onca), the largest South American felid. This unit focuses on the isolation and culture of fibroblasts from Jaguar skin and muscle biopsies, and ear cartilage dissection immediately after death to preserve one of the several endangered species in this biome. These culture techniques enabled us to contribute 570 samples from 45 autochthonous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 12 publications
(12 reference statements)
2
34
0
Order By: Relevance
“…The data of in vitro culture presented a very similar cell growth pattern for both jaguars, where cellular growth from the explants occurred in 9 and 10 days. These data were similar to that obtained by Mestre‐Citrinovitz et al (), who that reported that cell growth occurred between 10 and 14 days for the yellow jaguar. Furthermore, for other species of felines such as the Bengal tiger ( Panthera tigris tigris ) and Siberian tiger ( Panthera tigris altaica ), cell growth occurred after about 5–12 days of in vitro culture (Guan et al, ; Liu, Guo, Liu, Guan, & Ma, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The data of in vitro culture presented a very similar cell growth pattern for both jaguars, where cellular growth from the explants occurred in 9 and 10 days. These data were similar to that obtained by Mestre‐Citrinovitz et al (), who that reported that cell growth occurred between 10 and 14 days for the yellow jaguar. Furthermore, for other species of felines such as the Bengal tiger ( Panthera tigris tigris ) and Siberian tiger ( Panthera tigris altaica ), cell growth occurred after about 5–12 days of in vitro culture (Guan et al, ; Liu, Guo, Liu, Guan, & Ma, ).…”
Section: Discussionsupporting
confidence: 92%
“…We described the histological aspects of ear skin of the yellow and black jaguars, as this information is essential for a more targeted application of skin cryopreservation and subsequent cellular recovery. The formation of skin banks is of growing interest in conserving genetic samples of wild felids (Guan et al, ; León‐Quinto et al, ), especially jaguars (Mestre‐Citrinovitz et al, ), aimed at ensuring the storage of valuable genetic material (Praxedes, Borges, Santos, & Pereira, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular reprogramming for generating induced pluripotent stem cells (iPSCs) was recently adapted to reprogram diverse rare animal species, in an effort toward using this technology for preservation of the genetic material of endangered species. Successful trials resulting in generation of iPSCs from cryopreserved cell lines derived from populations of endangered Mandrillus leucophaeus, northern white rhinoceros, snow leopard were preformed (Leon-Quinto et al, 2009;Ben-Nun et al, 2011;Verma et al, 2012;Mestre-Citrinovitz et al, 2016). Somatic cells were reportedly used to clone a wild cat (Gómez et al, 2004).…”
Section: Introductionmentioning
confidence: 99%